HOW DOES EXPERIENCE INFLUENCE THE ACCEPTANCE OF ISLAMIC ACCOUNTING SOFTWARE AT KSPPS SIDOARJO REGENCY, EAST JAVA - Hidayat, Ujang Syaiful (Universitas 17 Agustus 1945 Surabaya, 2023)
This study examines how the management of Sharia Savings, Loan and Financing Cooperatives (KSPPS) of Sidoarjo Regional Office in East Java accepts the sharia-based accounting program. The Technology Acceptance Model (TAM) was used as the foundation of this study to evaluate system acceptance. This research was conducted in the Sidoajo regional office, where there are 40 KSPPS that are still operating, with the management of each KSPPS as the sample. Thus, the sample used was 120 core administrators. According to the research, experience has a positive effect on perceived usefulness or ease of use. In contrast, perceived ease of use is not significantly positive. Perceived ease of use has a positive impact on intention to use; however, perceived ease of use does not have a significant impact on intention to use.